Bilateral choanal atresia – An unusual case of severe respiratory distress in a newborn without nasal flaring - E Kuriakose, Mathews; Zacharias, Rekha; R, Athira (Indian Journal of Case Reports, 2022)
Respiratory distress in a newborn can be due to various causes and some need active intervention. Choanal atresia (CA) is a rare congenital anomaly with its incidence estimated to be 1 case/5,000–8,000 births. It is characterized by narrowing or blockage of the nasal passages. It is important to make an early clinical diagnosis with emphasis on timely management as it can be life-threatening. The pediatrician may be not able to pass a feeding tube through the neonate’s nostril even on repeated attempts. Detailed evaluation should be performed for the CHARGE association. High-resolution computed tomography can aid the diagnosis and transnasal endoscopic surgery is the preferred treatment modality. Here is a case report of a term neonate born with severe respiratory distress who was diagnosed to have bilateral CA on evaluation and managed with nasal endoscopic surgery.